2016
DOI: 10.4236/psych.2016.713158
|View full text |Cite
|
Sign up to set email alerts
|

Body Image Perception and Internalization Problems Indicators in Mexican Adolescents

Abstract: The aim of the study was to determine the existing differences by gender in the indicators of internalizing problems regarding the body image perception of Mexican adolescents. A descriptive and transversal study was developed. The participants were students from four public middle schools in Guadalajara Mexico. The instrument used was an online survey constituted by a sociodemographic section, an internalizing problems indicators scale (α = .85) and a body image perception scale (α = .70). Parental consent wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Comparisons with the models presented by the mass media and with their peers are likely to increase body image concerns in the young who perceive a gap between their own body image and the aesthetic ideal internalized. Internalizing symptoms may correlate with body dissatisfaction due to the sense of inadequacy experienced by adolescents with negative body image and because of the difficulty in social interaction and concerns about SOCIAL MEDIA AND THE MEDIATING ROLE OF BODY IMAGE CONCERNS peer acceptance often experienced by adolescents (Colunga-Rodríguez et al, 2016). As a result, adolescents trying to cope with these negative feelings are more at risk of being involved in unhealthy behaviors such as restrictive diet, excessive exercise, steroid or illicit drug consumption, excessive tanning etc.…”
Section: 1body Image Concerns and Internalizing Symptoms In Adolescencementioning
confidence: 99%
“…Comparisons with the models presented by the mass media and with their peers are likely to increase body image concerns in the young who perceive a gap between their own body image and the aesthetic ideal internalized. Internalizing symptoms may correlate with body dissatisfaction due to the sense of inadequacy experienced by adolescents with negative body image and because of the difficulty in social interaction and concerns about SOCIAL MEDIA AND THE MEDIATING ROLE OF BODY IMAGE CONCERNS peer acceptance often experienced by adolescents (Colunga-Rodríguez et al, 2016). As a result, adolescents trying to cope with these negative feelings are more at risk of being involved in unhealthy behaviors such as restrictive diet, excessive exercise, steroid or illicit drug consumption, excessive tanning etc.…”
Section: 1body Image Concerns and Internalizing Symptoms In Adolescencementioning
confidence: 99%
“…Body image dissatisfaction can be very different for males and females but is conceptually defined as a desire to change the appearance of one's body in any way, meaning the person may want to gain or lose weight (Kostanski et al., 2004). These body image problems are not only relevant during adolescence, but can also carry into adulthood (Colunga‐Rodríguez et al., 2016). Investigating how social media impacts the body image of children of different ages is an important topic which demands further attention.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are positive outcomes associated with social media use such as enhanced communication, the bridging of subcultures, and friendship maintenance (Siddiqui & Singh, 2016), exposure to social media content that promotes idealized appearances or body shapes can negatively impact adolescents. Indeed, research has shown that youth who spend more time on social media are also more likely to have body image concerns, disordered eating, lower self-esteem, and greater anxiety (Colunga-Rodríguez et al, 2016;Marengo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diferentes estudios indican una relación del estrés con diversos problemas de salud física y en general con una mayor probabilidad a enfermarse debido a que el estrés disminuye la eficacia del sistema inmunológico, así como también implica efectos en el individuo desde el aspecto emocional (10)(11)(12).…”
unclassified